PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA LEMBAGA KEUANGAN MIKRO SYARIAH - Alhifni, Anas (Jurnal Ekonomi dan Bisnis Islam, 2015)
The success of financial institute in achieving a good teamwork is based on leadership style and organization culture. This research aims to investigate the effect of leadership style and organizational culture toward LKMS performance (BMT). The method used in this research is structural equation modelling. The result of data analysis showed that organizational culture had the positive effect toward LKMS performance with a significant relation, yet leadership style had no effect toward LKMS performance, eventhough it still had effect toward LKMS performance based on indicators, as it was described in participatory indicator as much as 66,7% and dimentional indicator in orgazational culture granted the opportunity to develop as much as 60,6%.Â Keyword: Leadership style, Organization Culture, Syariah Microfinance Institution Performance.